PS-C01-10: BLOOD PRESSURE AND OUTCOMES OF TREATED MODERATE HYPERTENSION IN ELDERLY PATIENTS. (January 2023) - Kim, Ju Hyeon; Lim, Subin; Chung, Se Hwa; Yum, Yunjin; Joo, Hyung Joon; Kim, Yong Hyun; Kim, Eung Ju
Abstract : Objective: There is limited evidence of the growing population of elderly patients with hypertension, particularly the relationship between blood pressure (BP) and adverse outcomes. We sought to estimate outcomes according to attained BP in elderly patients treated for moderate hypertension. Design and method: This multicenter, retrospective study used the Korea University Medical Center database built on electronic health records from 2017 to 2020. Patients initiated with at least two antihypertensive drugs as combined therapy were followed up for 3 years. The patients were grouped by on treatment systolic BP (SBP) in 10 mmHg increments from less than 120 to 140 mmHg or more. The primary outcome was a composite of all cause mortality, myocardial infarction, and stroke. The relationships between attained BP and outcomes were assessed using adjusted Cox regression analyses and restricted cubic splines. Results: From Jan 2017 to Dec 2017, a total of 4760 patients aged over 75 years (mean age 79.9) were enrolled and grouped into SBP lower 120 mmHg (n = 1188), SBP 120 to 129 mmHg (n = 1221), SBP 130 to 139 mmHg (n = 1194), and SBP over 140 mmHg (n = 1157). After a median follow up of 4.5 years, the incidence of the primary outcome was lowest in individuals with SBP of 120 to 129 mmHg (9.2%, p = 0.087). The age adjusted hazard ratio for the primary outcome showed a J shaped relationship with on treatment SBP and diastolic BP. Conclusions: A J curve relationship between on treatment SBP and the composite outcome was found consistently. In real world practice, on treatment SBP less than 130 mmHg was associated with improved outcomes in the elderly with moderate hypertension.